2017
DOI: 10.18203/2320-1770.ijrcog20173454
|View full text |Cite
|
Sign up to set email alerts
|

A study of dengue fever in pregnancy and its maternal and fetal prognosis

Abstract: Background: Dengue is a vector borne viral disease. Female Anopheles mosquito is the vector for the disease. Recently, there is an increase in the incidence of dengue fever in adult population in South Asian countries. With increasing rate of adult dengue fever victims, the number of infected pregnant women has also been increased. Dengue, during pregnancy may be associated with various complications, including abortions, preterm delivery, maternal mortality, low birth weight, neonatal admissions and fetal ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…As expected, four patients closer to their expected date of delivery had more severe clinical symptoms and landed up in multiorgan failure. [1] Most common symptoms included fever with chills(92%),followed by myalgia(80%) and arthralgia similar to other studies. [8] Though 76% of patients tested positive for NS1Ag which is highest among our patients, not all of them tested positive but 24% of patients tested positive only for IgM Antibodies, suggesting that the patients had recent infection with ending of viremic phase.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As expected, four patients closer to their expected date of delivery had more severe clinical symptoms and landed up in multiorgan failure. [1] Most common symptoms included fever with chills(92%),followed by myalgia(80%) and arthralgia similar to other studies. [8] Though 76% of patients tested positive for NS1Ag which is highest among our patients, not all of them tested positive but 24% of patients tested positive only for IgM Antibodies, suggesting that the patients had recent infection with ending of viremic phase.…”
Section: Discussionsupporting
confidence: 85%
“…The four serotypes designated as DENV -1, DENV -2, DENV -3, DENV -4. [1] It is one of the most important vector borne diseases affecting countries like India, with the vector being the Aedes aegyptis mosquito. 40% of the world's population live in dengue prone zone, indicating the high risk and burden of carrying the disease.…”
Section: Introductionmentioning
confidence: 99%
“…A useful finding of our study was the predictive value of ocular findings in the diagnosis of dengue in our pregnant cohort. A separate study of pregnant women with dengue in northern India reported similar findings: 100% of the dengue patients had conjunctivitis, and 57% had eye pain (30). According to the World Health Organization, dengue should be considered in patients with a high fever and retroorbital pain (31)(32)(33)(34), but there is no specific mention of conjunctivitis as a trigger for dengue testing.…”
Section: Discussionmentioning
confidence: 96%
“…The average birth weight noted in our study was 2.44kgs. Gehlot H et al 9 reported an average birth weight of <2.5 kg in 16% cases. 8% of babies required NICU admission and 4% had IUFD.…”
Section: Discussionmentioning
confidence: 97%